Childhood diabetes mellitus in a rural tertiary hospital in North-West Nigeria - Umma Abdullahi Idris (Wolters Kluwer Medknow Publications, 2018)
Background: Childhood diabetes mellitus (DM) has been described among children in developed world, with a very scant report among African children, especially those in rural areas. Aim: This study aimed to describe the prevalence, presentation, and outcome of DM among children seen in a rural tertiary hospital in North-West Nigeria. Materials and Methods: This was a 10-year retrospective study of children with DM seen in the Pediatric Department of Federal Medical Centre, Birnin Kudu, Jigawa State, Nigeria. Relevant demographic data, clinical presentation, and outcome were extracted and analyzed. Results: Nine of the 6269 of the children admitted during the study period had Type 1 DM, giving a prevalence of 1.4/1000 admissions. The mean age was 12.7 years, with a slight female preponderance. The mean duration of symptoms prior to presentation was 13.7 days and all the patients presented with diabetes ketoacidosis (DKA). All the patients recovered fully and were discharged to endocrine clinic, but only three children are being followed up. Conclusion: DKA was the only mode of presentation among children with DM in this series, with surprisingly excellent outcome but a high default rate.